Neuropsychiatric events associated with montelukast in patients with asthma: a systematic review - Chris Wai Hang Lo; Swathi Pathadka; Simon Xiwen Qin; Lydia W.Y. Fung; Vincent Ka Chun Yan; Hei Hang Edmund Yiu; Chloe I. Bloom; Ian Chi Kei Wong; Esther Wai Yin Chan (European Respiratory Review, 2023)
Background: The United States Food and Drug Administration issued a black box warning on the mental health adverse effects of montelukast in 2020. Age-related effects on the risk of developing specific neuropsychiatric events in montelukast users remain largely unknown. Objective: To describe the risk of neuropsychiatric events associated with montelukast in adults and children with asthma. Methods: A systematic search of all studies investigating neuropsychiatric events in montelukast users was performed in PubMed, the Cochrane Library and Embase from inception to 7 September 2022. Animal studies and conference abstracts were excluded. Results: 59 studies (21 pharmacovigilance studies, four reviews from 172 randomised controlled trials, 20 observational studies, 10 case reports and four case series) evaluating neuropsychiatric events in patients with asthma on montelukast were reviewed. No significant association was shown between montelukast and suicide-related events in six of the observational studies. No association was found for depression as defined by the International Classification of Diseases 10th revision codes in three observational studies and a review of randomised clinical trials. However, findings from four studies using antidepressant prescriptions as the outcome identified significant associations. Consistent with nine pharmacovigilance studies, two large-scale observational studies revealed possible associations of montelukast with anxiety and sleeping disorders in adult patients with asthma, respectively. However, the results were not replicated in two observational studies on children. Conclusion: Montelukast is not associated with suicide- and depression-related events in asthma patients. Older adults may be particularly susceptible to anxiety and sleeping disorders.